2020
DOI: 10.1186/s12885-020-07012-y
|View full text |Cite
|
Sign up to set email alerts
|

The tumour microenvironment of the upper and lower gastrointestinal tract differentially influences dendritic cell maturation

Abstract: Background: Only 10-30% of oesophageal and rectal adenocarcinoma patients treated with neoadjuvant chemoradiotherapy have a complete pathological response. Inflammatory and angiogenic mediators in the tumour microenvironment (TME) may enable evasion of anti-tumour immune responses. Methods: The TME influence on infiltrating dendritic cells (DCs) was modelled by treating immature monocyte-derived DCs with Tumour Conditioned Media (TCM) from distinct gastrointestinal sites, prior to LPS-induced maturation. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 65 publications
1
8
0
Order By: Relevance
“…In addition, several studies have concluded that CRC explant tissue-conditioned medium inhibits LPS-induced in vitro DC maturation and function. In these assays, upregulation of costimulatory markers (CD80 and CD86) and PD-L1, and secretion of IL-12 and TNF-a was inhibited, while secretion of IL-10 was potentiated suggesting DCs acquire a tolerogenic phenotype (184)(185)(186)(187). One study even correlated stronger inhibition of DC maturation by CRC-conditioned medium with poorer survival in patients (186).…”
Section: Tumor-induced DC Dysfunctionmentioning
confidence: 99%
“…In addition, several studies have concluded that CRC explant tissue-conditioned medium inhibits LPS-induced in vitro DC maturation and function. In these assays, upregulation of costimulatory markers (CD80 and CD86) and PD-L1, and secretion of IL-12 and TNF-a was inhibited, while secretion of IL-10 was potentiated suggesting DCs acquire a tolerogenic phenotype (184)(185)(186)(187). One study even correlated stronger inhibition of DC maturation by CRC-conditioned medium with poorer survival in patients (186).…”
Section: Tumor-induced DC Dysfunctionmentioning
confidence: 99%
“…DCs are antigen-presenting cells capable of inducing a T cell response, and maturation levels have been associated with patient survival and response to targeted therapies in CRC patients [ 38 , 39 ]. It has previously been reported that the TME in CRC causes inhibition of DC maturation [ 40 , 41 ]. On the contrary, however, we found upregulation of DC maturation by the rectal cancer TME, which is in line with results published by Morrissey et al [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been reported that the TME in CRC causes inhibition of DC maturation [ 40 , 41 ]. On the contrary, however, we found upregulation of DC maturation by the rectal cancer TME, which is in line with results published by Morrissey et al [ 41 ]. This finding warrants further investigation since it may have important clinical implications in stratifying patients for whom immunotherapy may offer a clinical benefit.…”
Section: Discussionmentioning
confidence: 99%
“…66 Comparatively, in other studies, conditioned media from esophageal cancer cell lines was capable of reducing TNFa levels of lipopolysaccharideactivated dendritic cells. 67 This intriguing juxtaposition requires further attention but also necessitates the significant widening of the commercially available EAC cell P3 inflammasome and cytokine release. Pro-IL1b is cleaved by the inflammasome and caspase 1 into its active form, followed by release of both IL1b and TNFa from tissue resident monocytes and macrophages.…”
Section: Death or Regeneration: Tnfamentioning
confidence: 99%